2006
DOI: 10.1177/0309133306071957
|View full text |Cite
|
Sign up to set email alerts
|

Methods and uncertainties in bioclimatic envelope modelling under climate change

Abstract: International audiencePotential impacts of projected climate change on biodiversity are often assessed using single-species bioclimatic 'envelope' models. Such models are a special case of species distribution models in which the current geographical distribution of species is related to climatic variables so to enable projections of distributions under future climate change scenarios. This work reviews a number of critical methodological issues that may lead to uncertainty in predictions from bioclimatic mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
767
0
9

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 868 publications
(781 citation statements)
references
References 175 publications
5
767
0
9
Order By: Relevance
“…Despite their broad use, uncertainties about nichebased model predictions remain high (Hampe, 2004;Heikkinen et al, 2006;Randin et al, 2006). To date, the main drawback of niche-based models is their inability to consider important relationships such as biotic interactions, mortality, or growth (Davis et al, 1998;Hampe, 2004) and their reliance on observed distributions, which are the results of long-term historical factors (e.g., postglacial recolonization and human management), and environmental stochasticity, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…Despite their broad use, uncertainties about nichebased model predictions remain high (Hampe, 2004;Heikkinen et al, 2006;Randin et al, 2006). To date, the main drawback of niche-based models is their inability to consider important relationships such as biotic interactions, mortality, or growth (Davis et al, 1998;Hampe, 2004) and their reliance on observed distributions, which are the results of long-term historical factors (e.g., postglacial recolonization and human management), and environmental stochasticity, among other factors.…”
Section: Discussionmentioning
confidence: 99%
“…''Fill'' refers to the total fit of the matrix. Columns ''NODFcolumns'' and ''NODFrows'' refer to the NODF as measured only according to matrix columns and rows, respectively, while ''NODF'' refers to the total NODF variables, but a minimum set of available parameters have been chosen to avoid overfitting, which in turn may result in artifacts (Beaumont et al 2005;Heikkinen et al 2006;Araújo and Peterson 2012). The fact that the total contribution of the direct abiotic variables (i.e., soil, landscape and climate variables) in the model reaches 10.8 %, whereas bare soil and plant cover attain 14.1 and 0.1 %, respectively, also indicates that patterns resulting from disturbance and biotic interactions may also be important.…”
Section: Probability Of Occurrence and Biotic Interactionsmentioning
confidence: 99%
“…The relationships established between the variables may then be used to project the future distribution of the species under a set of climate change scenarios (Pearson and Dawson, 2003;Luoto et al, 2007). Such studies can provide a valuable initial assessment of likely climate change impacts, especially if used at coarse spatial scales where macro-climate variation has most impact on species distributions (Pearson and Dawson, 2003;Luoto et al, 2005;Heikkinen et al, 2006). There are, of course, limitations to such modeling (Pearson and Dawson, 2003;Beaumont et al, 2007;Brooker et al, 2007;Osborne et al, 2007a).…”
Section: Species Distribution Modelingmentioning
confidence: 99%